(untitled) (Ágora Journal, 2022)
The following text brings elements that may contribute to the debate on human rights and the ideological content that shapes its postulates, especially with its proclamation from the Universal Declaration of Human Rights of 1948. The objective is to highlight the importance of the historical construction and collective agreement of human rights in the face of the recognition of the dignity of the human person, as well as questioning how much its legal and political provisions are embargoed by the bourgeois ideology that makes its universally unfeasible, in a society whose foundation is the reproduction of substantive inequality between men and women.